Assessment of advanced demineralized bone fiber graft forms in rabbit posterolateral spine fusion: A feasibility study - Nelson Scarborough; Hania Shahzad; Brian Barnes; Safdar N. Khan (Journal of Orthopaedic Reports)
Background: Fibrant Fibers (FF) are a new type of demineralized bone fibers (DBF) that enable the production of novel graft forms such as the cylindrical graft Pak. The objective of this study was to evaluate the fusion rates of combinations of FF and Pak with autograft iliac crest bone graft (ICBG) and bone marrow aspirate (BMA) in a challenging posterolateral rabbit fusion model.1 These grafts are designed to create a continuous matrix across the fusion site, and easily incorporate autograft and BMA, acting as autograft extenders or substitutes when used with BMA. Methods: This feasibility study was conducted, recruiting eleven healthy, skeletally mature female white New Zealand rabbits who were randomly assigned to three groups: Group 1 received ICBG and FF, Group 2 received ICBG placed inside Pak, and Group 3 received FF rehydrated with BMA and placed inside FB. For each animal, grafts were implanted bilaterally along the transverse processes (TP). Primary outcomes were fusion rates assessed by manual palpation, radiographs, and 3D uCT images at 8 weeks. Results: All 11 animals successfully recovered from surgery. Fusion rates were found to be 91 % using manual palpation, with 100 % fusion observed in Group 1 and Group 3. Radiological evaluation showed fusion rates of 100 % for Group 1, 100 % for Group 3, and 90 % for Group 2. Micro CT evaluation revealed fusion rates of 100 % for all three groups. The quality of fusion was found to be robust across all three groups based on histological evaluation. Conclusions: The results of this feasibility study demonstrate the potential of DBF forms of FF, particularly when combined with BMA, shows promise as an effective alternative or adjunct to traditional autografts. The findings suggest that these graft forms could be highly beneficial in clinical settings, providing surgeons with more versatile and potentially more effective options for spinal fusion procedures.